Use these two trig identities:
#cottheta=costheta/sintheta#
#sectheta=1/costheta#
And the Pythagorean identity (and its variations):
#sin^2theta+cos^2theta=1#
#sin^2theta=1-cos^2theta#
Now, rewrite the problem in terms of sine and cosine, then simplify it down using the Pythagorean identity:
#color(white)=cot^4x(sec^4x-1)-2cot^2x#
#=cos^4x/sin^4x(1/cos^4x-1)-2*cos^2x/sin^2x#
#=(cos^4x)/sin^4x*1/(cos^4x)-cos^4x/sin^4x*1-2*cos^2x/sin^2x#
#=color(red)cancelcolor(black)(cos^4x)/sin^4x*1/color(red)cancelcolor(black)(cos^4x)-cos^4x/sin^4x-2*cos^2x/sin^2x#
#=1/sin^4x-cos^4x/sin^4x-2*cos^2x/sin^2x#
Getting a common denominator:
#=(1-cos^4x-2cos^2xsin^2x)/sin^4x#
#=(1-2cos^2xsin^2x-cos^4x)/sin^4x#
#=(1-cos^2xsin^2x-cos^2xsin^2x-cos^4x)/sin^4x#
#=(1-cos^2xsin^2x-cos^2x(sin^2x+cos^2x))/sin^4x#
#=(1-cos^2xsin^2x-cos^2x)/sin^4x#
Rewrite #1# as #sin^2x+cos^2x#:
#=(sin^2x+cos^2x-cos^2xsin^2x-cos^2x)/sin^4x#
#=(sin^2x+color(red)cancelcolor(black)(cos^2x)-cos^2xsin^2xcolor(red)cancelcolor(black)(color(black)-cos^2x))/sin^4x#
#=(sin^2x-cos^2xsin^2x)/sin^4x#
#=(sin^2x(1-cos^2x))/sin^4x#
#=(sin^2x*sin^2x)/sin^4x#
#=(sin^4x)/sin^4x#
#=1#
That's the proof. Hope this helped!